2018
DOI: 10.1523/jneurosci.0115-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between CSD-Evoked Metabolic Perturbations and Meningeal Afferent Activation and Sensitization: Implications for Mechanisms of Migraine Headache Onset

Abstract: The onset of the headache phase during attacks of migraine with aura, which occur in ∼30% of migraineurs, is believed to involve cortical spreading depression (CSD) and the ensuing activation and sensitization of primary afferent neurons that innervate the intracranial meninges, and their related large vessels. The mechanism by which CSD enhances the activity and mechanosensitivity of meningeal afferents remains poorly understood, but may involve cortical metabolic perturbations. We used extracellular single-u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 78 publications
(50 reference statements)
2
33
0
Order By: Relevance
“…46 The increased K + in the extracellular space upon K ATP channel activation can potentially diffuse into the leptomeninges and promote meningeal nociceptors activation. 48 Furthermore, K + channels have a substantial role in nociceptive processing, particularly in determining peripheral hyperexcitability (when closed) and neuronal inhibition (when opened). 48 Furthermore, K + channels have a substantial role in nociceptive processing, particularly in determining peripheral hyperexcitability (when closed) and neuronal inhibition (when opened).…”
Section: Discussionmentioning
confidence: 99%
“…46 The increased K + in the extracellular space upon K ATP channel activation can potentially diffuse into the leptomeninges and promote meningeal nociceptors activation. 48 Furthermore, K + channels have a substantial role in nociceptive processing, particularly in determining peripheral hyperexcitability (when closed) and neuronal inhibition (when opened). 48 Furthermore, K + channels have a substantial role in nociceptive processing, particularly in determining peripheral hyperexcitability (when closed) and neuronal inhibition (when opened).…”
Section: Discussionmentioning
confidence: 99%
“…Two patterns of prolonged nociceptor activation—biphasic activation (brief activation around SD induction followed by delayed, persistent activation, primarily in the Aδ population) and persistent activation with delayed onset (in C unit population)—were observed following SD [35]. SD-evoked prolonged activation of meningeal nociceptors might be related to ongoing basal activity or the number of receptive fields, rather than to the inflammatory and ATP chemosensitivity of the neurons; SD-evoked activation and mechanical sensitization of meningeal afferent responses was dissociated from SD-evoked metabolic perturbations [103]. SD was also found to evoke a delayed meningeal afferent mechanosensitization, which might explain nociceptive processes that underlie the worsening of migraine headache in conditions associated with transiently increased intracranial pressure [104].…”
Section: Experimental Methods Of Sd Inductionmentioning
confidence: 99%
“…These findings, together with the notion that reduced blood flow and tissue oxygenation lead to the sensitization of nociceptors in other tissues ( Hillery et al, 2011 , MacIver and Tanelian, 1992 , Mense and Stahnke, 1983 ), raises the possibility that the mechanisms responsible for driving dural nociceptors in the wake of CSD involve similar vascular and metabolic changes. We recently investigated this notion by recording the activity of dural nociceptors along with changes in cortical blood flow and tissue oxygenation following CSD ( Zhao and Levy, 2018b ). We have shown that cortical hypoperfusion and decreased oxygen availability coincide with the emergence of the prolonged activation and sensitization of dural nociceptors.…”
Section: Cortical Vascular and Metabolic Changes May Not Drive Mening...mentioning
confidence: 99%
“…While COX-derived prostanoids may not promote the CSD-evoked prolonged activation of dural nociceptors, we recently demonstrated COX involvement in mediating their mechanical sensitization ( Zhao and Levy, 2018b ). The mechanism by which COX-derived mediators promote the sensitization of dural nociceptors following CSD remains unclear.…”
Section: Cortical Vascular and Metabolic Changes May Not Drive Mening...mentioning
confidence: 99%
See 1 more Smart Citation